2009
DOI: 10.2353/ajpath.2009.080644
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Urinary L-Type Fatty Acid-Binding Protein Predicts Histological Severity of Acute Kidney Injury

Abstract: The present study aimed to evaluate whether levels of urinary L-type fatty acid-binding protein (L-FABP) could be used to monitor histological injury in acute kidney injury (AKI) induced by cis-platinum (CP) injection and ischemia reperfusion (IR). Different degrees of AKI severity were induced by several renal insults (CP dose and ischemia time) in human L-FABP transgenic mice. Renal histological injury scores increased with both CP dose and ischemic time. In CPinduced AKI, urinary L-FABP levels increased exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 22 publications
1
64
1
4
Order By: Relevance
“…In L-FABP transgenic mice, urinary L-FABP levels allowed the accurate and earlier detection of both histologic and functional insults in ischemia-induced AKI. 60 In contrast, heart-type FABP (H-FABP) is localized in the distal tubules, heart, small intestine, and skeletal muscles.…”
Section: Fatty Acid-binding Proteinsmentioning
confidence: 99%
“…In L-FABP transgenic mice, urinary L-FABP levels allowed the accurate and earlier detection of both histologic and functional insults in ischemia-induced AKI. 60 In contrast, heart-type FABP (H-FABP) is localized in the distal tubules, heart, small intestine, and skeletal muscles.…”
Section: Fatty Acid-binding Proteinsmentioning
confidence: 99%
“…Recent studies performed in children have shown that L-FABP is a sensitive biomarker in ischemic renal injury. 15 Few data are available regarding renal functional abnormalities in children with thalassemia. 2 There are very few studies that investigate renal dysfunction in patients with TM.…”
Section: Introductionmentioning
confidence: 99%
“…Total GFR was measured by plasma decay kinetics of FITC-inulin. 47,48 A bolus of around 4 ml/g body wt FITC-inulin was injected into the retro-orbital plexus of either vehicle-injected mice or LPS-injected mice, and blood was collected 1, 3, 5, 10, 15, 35, 55, and 75 minutes later. Plasma fluorescence was measured using a microplate reader (SH-9000; Corona, Ibaraki, Japan).…”
Section: Renal Functionmentioning
confidence: 99%